Recovery of Petroleum Brine-Contaminated Soil by Eleocharis sp. in a Tropical Marshland - Verónica Isidra Domínguez-Rodríguez; Francisco J. Guzmán-Osorio; Liliana Hernández-Acosta; Rodolfo Gómez-Cruz; J. Edmundo Rosique-Gil; Randy H. Adams (Tropical Life Sciences Research, 2024)
Almost all research on natural attenuation and phytoremediation of sites contaminated with briny produced water has been conducted in temperate climates, however, there is a dearth of information on the use of tropical species for this purpose. It is within this context, that we investigated a spontaneously growing hypersaline spikerush from a contaminated site in southeast Mexico, to determine its soil salinity limits, the relationship between soil organic matter and salinity, and for preliminary documentation of floristic succession with Typha sp. for phytoremediation o f brine s pills. Soil was sampled (0 cm–20 cm) three times between 2018–2021, focusing on the end of the dry season (most critical period). The species tentatively identified as Eleocharis mutata was tolerant to soil hypersalinity (Electrical Conductivity: 125 dS/m) and appeared to generate a cyclic process of succession to recover areas with soil salinity levels higher than it could otherwise tolerate. A salinity gradient was found between the most heavily contaminated part of the site (“kill zone”, > 212 dS/m), the first Eleocharis sp. individuals (125 dS/m), slowly advancing through the main spikerush stand, and finally into a cattail stand (< 8.02 dS/m). Similarly, an inverse relationship between Soil Organic Matter content and soil salinity was observed. This is the first time this species has been identified with a brine spill, its salinity limits determined, and investigated for use in phytoremediation of this kind.